Cross-dressing among medieval Ashkenazi Jews: Confirming challenged group borders - Roos, Lena (Nordisk judaistik/Scandinavian Jewish Studies, 2017)
This article deals with explicit permissions for two types of cross-dressing found in the thirteenth-century ethical tract Sefer Chasidim. In order to avoid being sexually assaulted, female Jewish travellers were allowed to disguise themselves as a. Christians, even as nuns, or b. men. This contradicts biblical and rabbinical prohibitions against such practices. These textual passages are discussed, set against the Jewish and Christian medieval discourse on dress and identity, and they are also related to other contemporary source texts that show that the borders between men and women, and Jews and Christians, as distinct and separate groups were at this time being contested. The author concludes that these permissions should not be seen as ways of transcending the boundaries of the group, but rather as part of a discourse that served to strengthen such boundaries.